2018
DOI: 10.1038/s41598-018-20993-y
|View full text |Cite
|
Sign up to set email alerts
|

Open-Label Placebo Treatment for Cancer-Related Fatigue: A Randomized-Controlled Clinical Trial

Abstract: The purpose of this 21-day assessor blinded, randomized-controlled trial was to compare an open-label placebo (OLP) to treatment as usual (TAU) for cancer survivors with fatigue. This was followed by an exploratory 21-day study in which TAU participants received OLPs while OLP participants in the main study were followed after discontinuing placebos. Cancer survivors (N = 74) who completed cancer treatment 6 months to 10 years prior to enrollment reporting at least moderate fatigue (i.e., ≥4 on a 0–10 scale) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 28 publications
(23 reference statements)
3
106
1
3
Order By: Relevance
“…This is counterintuitive since placebos supposedly work because people believe they do, but (presumably) knowing a treatment is a mere sugar pill makes it difficult to believe they will work. In spite of the lack of intuitive appeal, numerous studies have demonstrated that deception may not be needed to elicit placebo effects and have also demonstrated potential effectiveness at improving significant clinical outcomes in patients with irritable bowel syndrome (IBS) (Kaptchuk et al, 2010), chronic low back pain (Carvalho et al, 2016), depression (Park & Covi, 1965), attention-deficit hyperactivity disorder (ADHD) (Sandler, Glesne, & Geller, 2008), rhinitis (Schaefer, Harke, & Denke, 2016), and cancer-related fatigue (Hoenemeyer, Kaptchuk, Mehta, & Fontaine, 2018). …”
Section: Do Placebos Require Deception? the Mysterious Case Of Opementioning
confidence: 99%
See 3 more Smart Citations
“…This is counterintuitive since placebos supposedly work because people believe they do, but (presumably) knowing a treatment is a mere sugar pill makes it difficult to believe they will work. In spite of the lack of intuitive appeal, numerous studies have demonstrated that deception may not be needed to elicit placebo effects and have also demonstrated potential effectiveness at improving significant clinical outcomes in patients with irritable bowel syndrome (IBS) (Kaptchuk et al, 2010), chronic low back pain (Carvalho et al, 2016), depression (Park & Covi, 1965), attention-deficit hyperactivity disorder (ADHD) (Sandler, Glesne, & Geller, 2008), rhinitis (Schaefer, Harke, & Denke, 2016), and cancer-related fatigue (Hoenemeyer, Kaptchuk, Mehta, & Fontaine, 2018). …”
Section: Do Placebos Require Deception? the Mysterious Case Of Opementioning
confidence: 99%
“…Importantly, all these trials are characterized by the lack of blinding that can be achieved by comparing open placebos vs hidden placebos and the comparison with the best available treatment to estimate the relevance of open placebo potential effectiveness. Recently, open label placebos have been tested in 74 cancer survivors in a 21-day assessor blinded, randomized-controlled trial that compared an open-label placebo to TAU for fatigue (Hoenemeyer et al, 2018). Two placebo pills taken twice induced a 29% improvement in fatigue severity, and a 39% improvement in fatigue-disrupted quality of life.…”
Section: Clinical Open-label Placebo Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a recent randomized blinded controlled trial compared the use of OLP to the standard therapy for 74 cancer survivors with chronic fatigue. OLP participants reported a 29% improvement in fatigue severity and a 39% improvement in fatigue‐disrupted quality of life compared to the standard of care . In a systematic review of the five aforementioned OLP trials, a positive effect of OLP groups was found compared to no‐treatment groups .…”
Section: Mechanisms Of the Placebo Responsementioning
confidence: 98%